GENDER AND INVESTMENT BEHAVIOR: A REVIEW AND BIBLIOMETRIC ANALYSIS - Rina Suprina; Ikin Solikin; Budi Supriatono Purnomo; Nurbaeti Nurbaeti (Universitas Islam Lamongan, 2023)
The effect of gender differences on investment behavior is a research topic that needs to be explored to understand the phenomena. This paper is to review the literature on gender and investment behavior, as well as their influence on other dimensions. The Publish or Perish software was used to acquire literature data, and the Google Scholar database was chosen. The term used for the title is